1999
DOI: 10.1159/000018221
|View full text |Cite
|
Sign up to set email alerts
|

<i>Helicobacter pylori</i> and Behçet’s Disease

Abstract: Background: Recent investigation of the etiology of Behçet’s disease (BD) has focused on heat shock proteins (HSP) which belong to the HSP 60 family. Both the gastric pathogen Helicobacter pylori (HP) and BD may cause ulcers in the gastrointestinal tract and, HP expresses HSP 60. Objective: Whether HP is linked to the pathogenesis of BD or not, and to investigate the influence of HP eradication on clinical parameters of BD. Methods: Patients with BD were divided into two groups. Group I comprised 49 patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 4 publications
0
37
0
3
Order By: Relevance
“…This recently discovered bacterium, which colonizes the stomach (first cultivated in 1983), did not attract many ophthalmologists’ attention until recently. Anti- H.-pylori antibodies have been detected by ELISA in the sera of only 1 child with idiopathic bilateral uveitis [33], in Behcet’s disease [34], in glaucoma patients [35] as well as in central serous chorioretinopathy [36]. The debate about H. pylori as a possible cause of acne rosacea is also current.…”
Section: Introductionmentioning
confidence: 99%
“…This recently discovered bacterium, which colonizes the stomach (first cultivated in 1983), did not attract many ophthalmologists’ attention until recently. Anti- H.-pylori antibodies have been detected by ELISA in the sera of only 1 child with idiopathic bilateral uveitis [33], in Behcet’s disease [34], in glaucoma patients [35] as well as in central serous chorioretinopathy [36]. The debate about H. pylori as a possible cause of acne rosacea is also current.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, a patient with the BD, resistant to treatment, demonstrated a proportional remission after H. pylori eradication treatment suggesting that anti-H. pylori antibiotherapy can reduce the development of new oral aphthous ulcers and, for a limited time, the frequency of recurrent attacks in patients with BD [52]. Avc et al [53] found that although the H. pylori seroprevalence between patients with BD and controls was not significantly different, the number and size of oral and genital ulcers diminished significantly and various clinical manifestations regressed after the eradication of H. pylori. Moreover, endoscopic findings, eradication rate, and prevalence of H. pylori were shown similar in patients with BD and patients in the control group [54].…”
Section: Helicobacter Pylorimentioning
confidence: 99%
“…Hier scheinen noch die Reduktion von Beschwerden nach erfolgreicher Eradikationstherapie von HP zu überwiegen, wobei größere Studien mit Doppelblindansatz fehlen [19,20,21].…”
Section: Helicobacter Pyloriunclassified